Doxycycline poly e-caprolactone nanofibers in patients with chronic periodontitis - A clinical evaluation - Chaturvedi T.P.; Srivastava R.; Srivastava A.K.; Gupta V.; Verma P.K. (My University, 2025)
Aim: To develop a low-dose controlled-release delivery system for the treatment of periodontal infections. A new sustained release drug system of Poly e-caprolactone (PCL) nanofibers containing doxycycline (DOX) was successfully electrospun and evaluated clinically for periodontal diseases. The retentive doxycycline nanofibres were shown to provide a controlled delivery of the drug. Material and Methods: Nanofibers were prepared with DOX in PCL by electrospinning technique. The drug-coated nanofibres provided sustained effect up to a period of 11 days (264 h) and followed first order release. Forty sites in 7 patients (4 females and 3 males) with chronic periodontitis (5-8mm probing depth) were allocated in 2 experimental treatment groups, Group A-SRP (Scaling and Root Planing) + DOX nanofibers and Group B -SRP (Scaling and Root Planing) alone (control group). All these patients were evaluated clinically for probing depth (PD), plaque index (PI) and gingival index (GI). Results: Both the treatment groups were found to be efficacious in the treatment of periodontal disease as demonstrated by improvement in PD, PI and GI. Conclusion: Combination of SRP (Scaling and Root Planing) + DOX nanofibers (Group A) resulted in added benefits compared to the control group.